Genome-wide association study identifies a locus at 7p15.2 associated with endometriosis - Painter, J; Anderson, C; Nyholt, DR; MacGregor, S; Lin, J; Lee, S; Lambert, A; Zhao, Z; Roseman, F; Guo, Q; Gordon, S; Wallace, L; et al. (2011)
Endometriosis is a common gynecological disease associated with pelvic pain and subfertility. We conducted a genome-wide association study (GWAS) in 3,194 individuals with surgically confirmed endometriosis (cases) and 7,060 controls from Australia and the UK. Polygenic predictive modeling showed significantly increased genetic loading among 1,364 cases with moderate to severe endometriosis. The strongest association signal was on 7p15.2 (rs12700667) for 'all' endometriosis (P = 2.6 ×- 10-7, odds ratio (OR) = 1.22, 95% CI 1.13-1.32) and for moderate to severe disease (P = 1.5 ×- 10 -9, OR = 1.38, 95% CI 1.24-1.53). We replicated rs12700667 in an independent cohort from the United States of 2,392 self-reported, surgically confirmed endometriosis cases and 2,271 controls (P = 1.2 ×- 10 -3, OR = 1.17, 95% CI 1.06-1.28), resulting in a genome-wide significant P value of 1.4 ×- 10-9 (OR = 1.20, 95% CI 1.13-1.27) for 'all' endometriosis in our combined datasets of 5,586 cases and 9,331 controls. rs12700667 is located in an intergenic region upstream of the plausible candidate genes NFE2L3 and HOXA10. © 2011 Nature America, Inc. All rights reserved.